Effect of Concentration of Mangrove Leaf Extract Lumnitzera Racemosa on Hela Cell Viability - Ayu Kartika Fitri Ayu (Journal of Stem Cell Research and Tissue Engineering, 2022)
Cervical cancer is a disease caused by a malignant process that occurs in the cervix or cervix. The cause of cervical cancer is not known for certain, but it is estimated that around 95% is caused by HPV (Human Papilloma Virus). Efforts to cure cancer with drugs (pharmacotherapy) or with chemical compounds (chemotherapy) in general have not been able to give satisfactory results, so alternative treatment methods are sought, including traditional medicine, namely by using mangroves. Lumnitzera racemosa is one type of mangrove plant that has been used in alternative medicine because of its potential as anticancer. The aim of this study was to determine the effect of Lumnitzera racemosa mangrove extract on hela cell viability. Lumnitzera racemosa leaf powder was extracted using graded maceration. The solvents used include n-hexane, ethyl acetate, and ethanol. The results showed that the LC50 value was 56 ppm, it means that the ethanol extract has toxic properties. The results of the phytochemical test of the leaf extract of Lumnitzera racemosa contained alkaloids, steroids, triterpenoids and saponins. The test results showed that the extract yield was 11.58%, the water content of the extract was 22.17%, and the total phenol was 2742.17 mg GAE. The test results from the LC-MS test resulted in suspected compounds including pyrogallol, isoniazid and caffeine. The ethanolic extract of Lumnitzera racemosa leaf was cytotoxic to the viability of hela cells with the resulting IC50 value of 493.33 µg/mL.